Obstacles to growth among manufacturing firms in Malaysia - Subhan, Nadia Aquidah (2018)
This management project explores the obstacles to growth among manufacturing firms of different sizes in Malaysia. The hypotheses developed for this management project includes as firms get older and bigger in size, they gain more knowledge, become more organized and their growth rate tend to be slower, and manufacturing firm growth rate change over a firm’s life course depending on the obstacles faced by each individual firm. Using data from Enterprise Surveys done by the World Bank for Malaysia, regressions analysis was applied to study the effect of size, age, access to land, business licensing and permits, courts, customs and trade regulations, labour regulations, practices of competitors in the informal sector, tax rates and transport on firm’s growth. The results shows that small and young firms tend to grow faster as compared to the larger and older firms. Obstacles from access to land, business licensing and permits, corruption, courts, customs and trade regulations, labour regulations, political instability, practices of competitors in the informal sector, tax rates to transport have negative correlation with growth of manufacturing firms in Malaysia, except for large sized firm’s growth with corruption and political instability that has positive correlation.